2019
DOI: 10.1038/s41598-019-51622-x
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Streptomyces spp. from mangrove forest of Sarawak (Malaysia) and screening of their antioxidant and cytotoxic activities

Abstract: Streptomycetes have been the center of attraction within scientific community owing to their capability to produce various bioactive compounds, for instance, with different antimicrobial, anticancer, and antioxidant properties. The search for novel Streptomyces spp. from underexplored area such as mangrove environment has been gaining attention since these microorganisms could produce pharmaceutically important metabolites. The aim of this study is to discover the diversity of Streptomyces spp. from mangrove i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 101 publications
1
33
0
3
Order By: Relevance
“…In recent years, the search for Streptomyces is concentrated on the rather less explored ecological niches such as the mangrove forest to increase chances of finding new Streptomyces species with bioactive potentials [24,56,57]. An earlier study by Ser, et al [37] demonstrated the large genome size of Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, the search for Streptomyces is concentrated on the rather less explored ecological niches such as the mangrove forest to increase chances of finding new Streptomyces species with bioactive potentials [24,56,57]. An earlier study by Ser, et al [37] demonstrated the large genome size of Streptomyces sp.…”
Section: Discussionmentioning
confidence: 99%
“…A rich biodiversity translates to a rich chemical diversity, and this is evidenced in that various resources are derived from mangroves and utilized in traditional medicines [23]. The microbiological diversity in the mangrove soil, particularly the Streptomyces, and their biosynthetic potentials remain underexplored [24]. Many of the lead compounds reported from mangrove forests were isolated from endophytic fungi with few reported from Streptomyces [25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies demonstrated that radical scavengers like vitamin E, in the form of tocopherol and tocotrienol, can protect the glutamate-injured cells from oxidative stress. Other than vitamin E, other sources such as microbial resources were also demonstrating strong antioxidants [116][117][118][119][120][121][122][123][124][125][126] and neuroprotective properties [127][128][129][130][131][132] such as metal chelating and radical scavenging potentials [133][134][135][136][137][138][139][140] . In conclusion, neuronal cell seemed to be the most vulnerable brain cells toward glutamate toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Desferrioxamine B as a siderophore is capable of chelating iron and has been used clinically to treat iron overdose. Additionally, desferrioxamine can prevent oxidative stress by preventing accumulation of free radicals [54][55][56][57][58][59][60][61] . These actions, in turn enabled, desferrioxamine to be able to reduce occurrence of cancer and neurodegenerative diseases like Parkinson's disease and Alzheimer's disease by preventing inflammation including regulating activation of microglial cells which are capable of producing pro-inflammatory cytokine.…”
Section: Data Descriptionmentioning
confidence: 99%